2014
DOI: 10.1089/rej.2013.1478
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vasoactive Intestinal Peptide in Chronic Obstructive Pulmonary Disease with Pulmonary Hypertension

Abstract: In the patients with COPD and PH and in particular in the group of OP PH, VIP is significantly increased, probably to correct the imbalance between vasoconstrictor and vasodilatator mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In smoking COPD patients, increased expression of VIP was reported in the patients' epithelium, while it was downregulated in their airway smooth muscle cell layer as compared to smokers without COPD [22]. A similar increase in VIP was reported in arterial serum samples obtained from patients with COPD and pulmonary arterial hypertension (PAH) [23]. …”
Section: Introductionmentioning
confidence: 71%
“…In smoking COPD patients, increased expression of VIP was reported in the patients' epithelium, while it was downregulated in their airway smooth muscle cell layer as compared to smokers without COPD [22]. A similar increase in VIP was reported in arterial serum samples obtained from patients with COPD and pulmonary arterial hypertension (PAH) [23]. …”
Section: Introductionmentioning
confidence: 71%
“…As an important neuropeptide, VIP shows potent anti-inflammatory and immunomodulatory activities that affect both innate and adaptive immunity ( 40 ) and plays a critical role in the maintenance of the respiratory system homeostasis. Several animal and clinical trials suggest that VIP or VIP agonist treatment could be used for respiratory diseases, including acute lung injury, allergic asthma, and COPD ( 46 48 ). Our previous study showed that RSV-induced antiviral responses in KCF mice peak at 12 h postinfection, consistent with other research showing that IFN-α/β acts as a rapid-response cytokine upon RSV infection ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research can be focused on the hypothesis that biomarkers can help clinicians to phenotype patients suffering from different forms of PH (e.g., interstitial lung disease, chronic obstructive pulmonary disease with PH [107,108], and advance HF with PH) and possibly direct them to specific drugs other than pulmonary vasodilators [109].…”
Section: Future Developmentsmentioning
confidence: 99%